1987
DOI: 10.1016/0166-5316(87)90057-5
|View full text |Cite
|
Sign up to set email alerts
|

Waiting-time approximations in multi-queue systems with cyclic service

Abstract: This study is devoted to mean waiting-time approximations in a single-server multi-queue model with cyclic service and zero switching times of the server between consecutive queues. Two different service disciplines are considered: exhaustive service and (ordinary cyclic) nonexhaustive service. For both disciplines it is shown how estimates of the mean waiting times at the various queues can be obtained when no explicit information on arrival intensities and service-time distributions is available, while only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…We applied the approximation for the mean end-to-end delay per type to a model based on a Network on Chip using the Boxma-Meister approximation [6] to obtain the necessary single-station results. Although the Boxma-Meister approximation is less accurate for asymmetric systems, we could still accurately approximate the mean type i j end-to-end delay up to moderately high loads (around 0.7) in an asymmetric case study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied the approximation for the mean end-to-end delay per type to a model based on a Network on Chip using the Boxma-Meister approximation [6] to obtain the necessary single-station results. Although the Boxma-Meister approximation is less accurate for asymmetric systems, we could still accurately approximate the mean type i j end-to-end delay up to moderately high loads (around 0.7) in an asymmetric case study.…”
Section: Resultsmentioning
confidence: 99%
“…We give the approximation proposed by Boxma and Meister [6] for 1-limited polling systems. Although their analysis is aimed at continuous-time systems, it can easily be established that the key steps in their derivation are valid for discrete-time systems as well.…”
Section: -Limitedmentioning
confidence: 99%
“…Of those, we found that the Boxma-Meister [9] and Levy-Groenendijk [16] approximations could be extended to the discrete-time domain without much additional effort. We will compare our approximation with these two approximations in Section 5.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Other authors, such as Boxma and Meister [9], Fuhrmann and Wang [15], Levy and Groenendijk [16], and Srinivasan [26], only approximated mean waiting times in cyclic 1-limited polling systems (and by Little's law, mean queue lengths). Of those, we found that the Boxma-Meister [9] and Levy-Groenendijk [16] approximations could be extended to the discrete-time domain without much additional effort.…”
Section: Relevant Literaturementioning
confidence: 99%
“…In deriving this approximation, we aim to fulfill the following criteria, which was proposed by Boxma and Meister in [35]: (i) It is exact in the completely symmetric case, by which we mean the arrival distributions for all classes are identical; the service distributions for all classes are also identical; all queues are served with the same probability when they are nonempty and polled by the server, i.e. ½ ¾ for the two-class case.…”
Section: Approachmentioning
confidence: 99%